162 Multi-modality imaging in survivors of COVID-19. (4th June 2021) - Singh, Trisha; Joshi, Shruti; Spath, Nick; Kershaw, Lucy; Baker, Andy; Jordan, Helen; Gulsin, Gaurav; Williams, Michelle; van Beek, Edwin; Arnold, Jayanth; Scott, Semple; Newby, David; et al.
Abstract : Background: Widespread abnormalities of the myocardium have been reported in patients with COVID-19. However, these patients often have substantial co-morbidities and it is essential to understand whether cardiac abnormalities represent pre-existing disease or are the consequence of COVID-19. Objective: To determine the contribution and cardiac impact of co-morbidities in patients who have recovered from COVID-19. Methods: In a prospective observational study, adult patients hospitalized with confirmed COVID-19 were recruited from the Edinburgh Heart Centre between May and November 2020 and compared to healthy and co-morbidity-matched volunteers. Patients underwent gadolinium and manganese-enhanced magnetic resonance imaging and coronary computed tomography angiography. Results: Twenty-three patients (54±11 years, 20 male) who recovered from COVID-19 were recruited. Half (n=11, 48%) required admission to the intensive care unit and a third (n=7, 31%) received non-invasive or invasive ventilation. Patients had a high prevalence of known cardiovascular disease (n=18, 78%), associated risk factors (n=11, 45%) and coronary artery disease (n=8, 35%). Compared with younger healthy volunteers (n=10), myocardial native T1 values (1202±25 versus 1162±27 ms, P=0.008, figure 1 ) and extracellular volume fraction (31.9±1.7 versus 29.8±0.5 %, P=0.001, figure 1 ) were higher with no differences in manganese uptake. Compared to co-morbidity-matched volunteers (n=20), there were no differences in native T1 values (1202±25 versus 1196±39 ms, P=0.61, figure 1 ), extracellular volume fraction (31.9±1.7 versus 31.0±0.5 %, P=0.11), presence of late gadolinium enhancement or manganese uptake. These findings remained irrespective of COVID-19 disease severity, presence of concomitant myocardial injury or coronary artery disease. Conclusions: Patients who have recovered following hospitalization with COVID-19 have no evidence of a major excess in myocardial injury or dysfunction compared to co-morbidity-matched volunteers. The presence of co-morbidities likely explains many of the previously reported myocardial abnormalities. Conflict of Interest: None